LEARNING OBSTACLES ANALYSIS ON MULTIPLICATION OF NATURAL NUMBERS IN ELEMENTARY SCHOOL - Rohimah, Siti Maryam; Anaya, Salma Nur; Putri, Sarah Anida; Nurdiansah, Yusup (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
This research aims to find learning obstacles students experienced during natural number multiplication lessons in third-grade elementary school. Learning obstacles were obtained from the Respondent Ability Test (RAT) analysis on students who had studied the lessons on multiplication of natural numbers. The method used in this research is a qualitative descriptive method. The subjects were respondents who participated in RAT, namely 22 third-grade elementary school students in Bandung, Indonesia. Data collection techniques use tests, interviews, and documentation. Data analysis techniques include data collection, reduction, display, and conclusion. Learning obstacles found in natural number multiplication lessons are categorized into three types, namely ontogenic, epistemological, and didactical obstacles. Ontogenic obstacles occur when there is a gap in the students' thinking when analyzing concrete to abstract concepts. Epistemological obstacles may occur if students need help to apply the concepts they have learned in the context of story problems. Didactical obstacles happen when the learning carried out by teachers is only procedural, so students only memorize each multiplication result. Therefore, it is essential to analyze these learning obstacles and find the causes as a reference in finding solutions to design future learning tools that prevent these learning obstacles from happening.